2017
DOI: 10.18203/2349-2902.isj20170987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative pain relief with intra-peritoneal bupivacaine instillation in laparoscopic cholecystectomy- a randomized control study

Abstract: Background: Laparoscopic cholecystectomy is the surgical procedure of choice for symptomatic cholelithiasis due to the improved postoperative course, but patients undergoing laparoscopic cholecystectomy during the first 24 hours postoperatively complaints of pain. This study was designed to study the efficacy of intraperitoneal bupivacaine in reducing the initial postoperative pain and also to evaluate the postoperative shoulder tip pain, nausea and vomiting.Methods: Patients undergoing laparoscopic cholecyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The variation in heart rate and mean arterial pressure between the groups does not show statistically significant difference (p > 0.05). The results correlate to the study done by Agrawal S et al 15 who evaluated postoperative pain relief with intra-peritoneal bupivacaine instillation in laparoscopic cholecystectomy. The observed mean heart rate, systolic blood pressure, diastolic blood pressure between both groups was statistically not significant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The variation in heart rate and mean arterial pressure between the groups does not show statistically significant difference (p > 0.05). The results correlate to the study done by Agrawal S et al 15 who evaluated postoperative pain relief with intra-peritoneal bupivacaine instillation in laparoscopic cholecystectomy. The observed mean heart rate, systolic blood pressure, diastolic blood pressure between both groups was statistically not significant.…”
Section: Discussionsupporting
confidence: 87%
“…The local anaesthetic inhibits nociception by affecting nerve membrane associated proteins and by inhibiting the release and action of prostaglandins and other agents that sensitize or stimulate the nocicepters and contribute to inflammation. 15 However, absorption from dura meninge surface may also occur, which may be a further mechanism of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…7 A more recent study by Agrawal in 2017 also showed that there was no significant difference in postoperative pain scores between bupivacaine and control group in the immediate postoperative period following laparoscopic cholecystectomy. 8 This is in contrast to a similar study in Egypt in 2002 done by Shalan et al for laparoscopic pelvic surgery, who found that pain score and the analgesic dose required were lower in bupivacaine group. 9 Hasaniya et al in 2001 also studied the effect of preincisional bupivacaine instillation and concluded that the mean pain scores were lower as compared to controls at 4th and 24th hour postoperatively.…”
Section: Discussionmentioning
confidence: 55%
“…They found no statistically significant difference in systolic and diastolic blood pressure between study groups. Similarly, Agrawal et al evaluated postoperative pain relief with intra-peritoneal bupivacaine instillation in laparoscopic cholecystectomy and observed that hemodynamic parameters were statistically not significant between the groups [ 19 ].…”
Section: Discussionmentioning
confidence: 99%